1997
DOI: 10.1097/00001756-199704140-00035
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of oxidative stress by antioxidants and resveratrol in PC12 cells

Abstract: The goal of this study was to investigate the effect of resveratrol, an active ingredient found in grapes and other plant products, in ameliorating oxidative stress. Oxidative stress was induced by addition of Fe2+ and t-butyl hydroperoxide to the cultured PC12 cell medium. Resveratrol, vitamins C and/or E, were added to the cell culture medium during oxidative stress. The combination of resveratrol and vitamins C and/or E was more effective in protecting the cell than was any of these three antioxidants alone. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
86
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(94 citation statements)
references
References 6 publications
3
86
0
1
Order By: Relevance
“…Recently, resveratrol was found to be a highly potent antioxidant which could inhibit free radical generation in brain, spinal cord, kidney, liver and red cell membrane [35][36][37][38] . It has been shown that resveratrol inhibits lipid peroxidation [39] , and prevents apoptotic cell death induced by oxidative stress [40] . The end production of lipid peroxidation includes aldehydes, hydrocarbon gases, and MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, resveratrol was found to be a highly potent antioxidant which could inhibit free radical generation in brain, spinal cord, kidney, liver and red cell membrane [35][36][37][38] . It has been shown that resveratrol inhibits lipid peroxidation [39] , and prevents apoptotic cell death induced by oxidative stress [40] . The end production of lipid peroxidation includes aldehydes, hydrocarbon gases, and MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, resveratrol was found to be a highly potent antioxidant that could inhibit free radical generation in the brain, spinal cord, heart, kidney, liver, red cell membrane, and so on [19,36,[44][45][46][47][48][49] . It has been shown that it inhibits lipid peroxidation [50] , and prevents apoptotic cell death induced by oxidative stress [51,52] . It has been postulated that resveratrol could supress mitochondria-induced production of ROS in rat brain [53] , protect DNA from oxidative damage in stroke-prone hypertensive rats [54] , and could inhibit neuronal loss after ischemia/reperfusion injury in gerbils [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Later on, trans-resveratrol was found to be the most effective extract from grape skin and seed, as well as a variety of other plants such as peanuts and berries, that produces beneficial health effects. To assess its role as an antioxidant, resveratrol was compared with the classical antioxidative vitamins C and E in a 1977 study (Chanvitayapongs et al, 1997). In this study, oxidative stress was induced by addition of Fe2+ and t-butyl hydroperoxide to the cultured PC12 cell medium.…”
Section: Resveratrolmentioning
confidence: 99%